2022
DOI: 10.3389/feduc.2022.920985
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Research on Individual Teacher-Child Relationships: A Chronological Review of Prominent Attachment-Based Themes

Abstract: Attachment theory has played a prominent role in the study of affective relationships between teachers and individual children in school settings. This review synthesizes three decades of attachment-based research on teacher-child relationships roughly covering the period between 1992 and 2022. Five key themes were discussed: (1) conceptualization and assessment, (2) secure base and autonomous exploration, (3) safe haven and self-regulation, (4) attachment history and relationship (dis)continuity, and (5) teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 141 publications
0
5
0
1
Order By: Relevance
“…Initially defined by Ainsworth et al (1974) , sensitive responsiveness refers to a caregiver’s ability to notice, interpret, and respond promptly and appropriately to an individual child’s signals. This concept has been extended to TSR, where teacher sensitivity also predicts the quality of the relationship ( Spilt and Koomen, 2022 ). However, it has been observed that caregiver or teacher sensitivity may not be present in some cultural contexts, as it does not align with local values ( Keller et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially defined by Ainsworth et al (1974) , sensitive responsiveness refers to a caregiver’s ability to notice, interpret, and respond promptly and appropriately to an individual child’s signals. This concept has been extended to TSR, where teacher sensitivity also predicts the quality of the relationship ( Spilt and Koomen, 2022 ). However, it has been observed that caregiver or teacher sensitivity may not be present in some cultural contexts, as it does not align with local values ( Keller et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, United States mothers tend to direct their children toward objects in the environment, promoting independent exploration ( Bornstein et al, 2012 ). Consequently, teachers in collectivistic cultures may encourage children to rely on adults for guidance and support, resulting in a greater tolerance for emotional dependency, and emotional dependency may be viewed as similar to closeness ( Gregoriadis et al, 2021 ; Spilt and Koomen, 2022 ; Vahidi et al, 2022 ). In contrast, individualistic cultures prioritize independence and separation of the self from the social context.…”
Section: Discussionmentioning
confidence: 99%
“…Tanpa adanya self-regulation orang dewasa baik emosi maupun perilaku dalam lingkungan sekolah yang jenuh, self-regulation anak juga akan terhambat (Spilt & Koomen, 2022). Self-regulation dapat berdampak dalam rasa tanggung jawab anak dan membantu guru dalam profesionalitasnya (Sáez-Delgado et al, 2022).…”
Section: Pendahuluanunclassified
“…Research about parent–child relationships is relevant because it also concerns children's relationships with important adults in their lives. Furthermore, early research about affective teacher–child relationships was based on theory and research about parent–child relationships (Spilt & Koomen, 2022; Verschueren & Koomen, 2012). Although peer relationships are less comparable to teacher‐child relationships as peer relationships are more egalitarian, research on peer relationships could still provide meaningful insight for the present study.…”
Section: Introductionmentioning
confidence: 99%